Local Peroxynitrite Formation Contributes to Early Control of Cryptosporidium parvum Infection - Gookin, Jody L. (American Society for Microbiology, 2005)
In intestinal inflammation, mucosal injury is often exacerbated by the reaction of NO with neutrophil-derived superoxide to form the potent oxidant peroxynitrite. Peroxynitrite also has antimicrobial properties that aid in the killing mechanism of macrophages and neutrophils. Cryptosporidium parvum parasitizes intestinal epithelium, resulting in loss of epithelial cells and mucosal inflammation. Synthesis of NO is significantly increased and arises from the induced expression of inducible nitric oxide synthase (iNOS) by the infected epithelium. Inhibition of iNOS results in intensified epithelial parasitism and oocyst excretion. We hypothesized that formation of peroxynitrite is restricted to sites of iNOS expression by the epithelium and contributes to host defense in C. parvum infection. Accordingly, the location and biological effects of peroxynitrite formation were examined in neonatal piglets infected with C. parvum. Infected piglets were treated daily with a selective iNOS inhibitor [L-N6-(1-iminoethyl)-lysine] or one of two peroxynitrite scavengers [5,10,15,20-tetrakis(N-methyl-4′-pyridyl)porphyrinato iron(III) or uric acid] or received vehicle. At peak infection, peroxynitrite formation was restricted to sites of iNOS expression by parasitized epithelium and lamina propria of the apical villi. Peroxynitrite formation was dependent on iNOS activity and was inhibited by treatment with peroxynitrite scavengers. Scavengers increased the number of intracellular parasites and the number of infected epithelial cells present per villus and significantly exacerbated oocyst excretion. Recovery from infection was not delayed by ongoing treatment with scavenger. The present results are the first to demonstrate an in vivo role for peroxynitrite formation in acute mucosal defense against a noninvasive intestinal epithelial pathogen.